Is Primary Hyperparathyroidism a Risk Factor for Papillary Thyroid Cancer? An Exemplar Study and Literature Review - Cinamon,Udi (2015)
Introduction Primary hyperparathyroidism (PHPT) is associated with several cancer types, including papillary thyroid carcinoma (PTC). Objective To explore further the relation between PHPT and PTC. Methods By considering patients with PHPT as extra-suspicious for PTC, we studied an exemplar group of patients with PHPT with a small (1 cm) thyroid nodule, which was negative in preoperative cytologic examination. During parathyroidectomy, a frozen section biopsy of the thyroid nodule confirmed PTC, as did the final surgical specimen, revealing that the preoperative cytology was false-negative. Additionally, relevant reports retrieved from the English literature addressing thyroid cancer and hyperparathyroidism were reviewed and processed. Results Four patients with PHPT were studied. Three had a multifocal thyroid disease, and three had neck lymph node metastasis. Processing previous report data supported an association between PHPT and PTC. Although thyroid nodularity among patients with PHPTwas similar to the general population, PTC incidence was higher. This was true also for patients with secondary hyperparathyroidism. Conclusions This study emphasized that PHPT should be considered as a noteworthy risk factor for PTC. Fine needle aspiration of a thyroid nodule is the most valuable diagnostic procedure for thyroid cancer. Yet, false-negative results were reported in up to 10% of cases, especially in small, subcentimeter nodules. In line with our data and the literature, patients with PHPT should have both a detailed ultrasound addressing the thyroid and cytology of any thyroid nodule, including small subcentimeter lesions. Moreover, surgical flexibility, allowing intraoperative thyroid nodule sampling, should be considered even for "innocent" nodules.